Analisis Peran Pegelolaan Pinjaman Terhadap Pertumbuhan Koperasi Suru Pudi Koting Dan Peningkatan Kesejahteraan Anggota - dua, Dominika; Mitan, Wilhelmina; De Romario, Fransiscus (Jurnal Projemen UNIPA, 2026)
Loan management is one of the important aspects of cooperative financial management because it plays a role in supporting the growth of the cooperative and improving member welfare. This study aims to analyze the role of loan management at Koperasi Suru Pudi Koting and its impact on member welfare. The research method used is qualitative descriptive. Data collection was conducted through observation, interviews, and documentation, while data analysis was carried out by relating field findings to theories of financial management, cooperative growth, and member welfare. The results of this study show that loan management at KSP Kopdit Suru Pudi Koting has been implemented through stages of loan feasibility assessment, establishment of loan procedures and policies, as well as supervision and loan collection. This loan management contributes to the growth of the cooperative, reflected in the increase in assets, business volume, and the remaining business results (SHU). In addition, loan management also has an impact on improving members' welfare through easier access to capital, increased income, and the quality of cooperative services.